2015
DOI: 10.4103/1319-2442.164607
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of dialysis practice-patterns in patients with chronic kidney disease on maintenance hemodialysis

Abstract: We studied the dialysis practice-patterns with regard to various aspects of chronic kidney disease (CKD) stage 5D, like anemia, mineral bone disease, vaccination, hospitalization, hypertension and cost of therapy. Four hundred and sixty-four adult hemodialysis (HD) patients from various dialysis centers of Mumbai were included in the study. The mean age of the study patients was 47.2 years. Temporary dialysis catheters were the most common initial vascular access. Thirteen percent of prevalent HD patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Although ACEI have the greatest impact on the regression of the left ventricular mass index in HD patients [20], they can cause undesirable hyperkalemia, which may be associated with sudden death due to cardiac arrhythmia, although the most recent studies indicate that this is due to hypokalemia more often than due to hyperkalemia [21], which is a possible reason for the small percentage of our subjects who took ACEI/sartans (18.8%). Other data in the literature indicate that the percentage of ACEI in the treatment of hypertensive HD patients varies significantly, from markedly low, as in our study [22,23], to over 50% [24]. Beta blockers were the most commonly prescribed antihypertensives in our study (39.8%).…”
Section: Discussionmentioning
confidence: 53%
“…Although ACEI have the greatest impact on the regression of the left ventricular mass index in HD patients [20], they can cause undesirable hyperkalemia, which may be associated with sudden death due to cardiac arrhythmia, although the most recent studies indicate that this is due to hypokalemia more often than due to hyperkalemia [21], which is a possible reason for the small percentage of our subjects who took ACEI/sartans (18.8%). Other data in the literature indicate that the percentage of ACEI in the treatment of hypertensive HD patients varies significantly, from markedly low, as in our study [22,23], to over 50% [24]. Beta blockers were the most commonly prescribed antihypertensives in our study (39.8%).…”
Section: Discussionmentioning
confidence: 53%
“…In this study more than two-third (68.2%) of the patients were on thrice-weekly dialysis and 31.2% were on twice-weekly dialysis which correlated with the findings of Kulkarniet al who found about 77% of the patients were on thrice-weekly dialysis and 23% were on twice-weekly dialysis. 9 But Perez-Garcia R et al found in ANSWER study 97% patient on thrice weekly hemodialysis. 8 Anoop G et al found hemodialysis sessions were thrice-weekly in 75% of the patients, twice-weekly in 21.9%, and four times weekly in 2.7% of the patients but in our study no patients were on four times weekly dialysis.…”
Section: Discussionmentioning
confidence: 97%
“…10 In this study, we found the vascular access at initiation of dialysis was temporary catheter in 91.6% of patients and AV fistula in 8.4% of the patients which was correlated with findings of Kulkarni MJ et al who found 90% of CKD patient initiate dialysis with temporary catheter and only 10% patient with AV fistula in India. 9 Anoop G et al found only in 15.5% patients dialysis were initiated with AVF, while 84.5% were initiated with temporary catheters. 10 Perez-Garcia R et al found 16% patient initiate dialysis through permanent catheter, 30% with temporary catheter, 51% with AV fistula, and 2% with AV graft.…”
Section: Discussionmentioning
confidence: 99%
“…About 56.33% of our study population had unknown etiology as the leading cause of hypertension (22.15%) as the second leading cause of end stage renal disease. An earlier report published by MJ Kulkarni et al also proposed unknown etiology as the leading cause and diabetic nephropathy as the second leading cause of endstage renal disease [4]. Late diagnosis of renal failure is a worldwide phenomenon, more so in developing countries like India (65%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…These samples help us to obtain a better understanding of the variation in practice patterns across different facilities. Studies have shown improved patient survival with higher dialysis dose and different dialysis membrane, thereby concluding that dialysis outcome can be modified by changes in dialysis practice [4]. Therefore, our study focuses on the dialysis practice pattern in patients undergoing hemodialysis in a tertiary and a private hospital.…”
Section: Introductionmentioning
confidence: 99%